Hybrid Breeding for Restoration of Threatened Forest Trees: Evidence for Incorporating Disease Tolerance in Juglans cinerea - Brennan, Andrea N.; McKenna, James R.; Hoban, Sean M.; Jacobs, Douglass F. (Frontiers in Plant Science, 2020)
Hybridization is a potential tool for incorporating stress tolerance in plants, particularly to pests and diseases, in support of restoration and conservation efforts. Butternut (Juglans cinerea) is a species for which hybridization has only recently begun being explored. This North American hardwood tree is threatened due to Ophiognomonia clavigignenti-juglandacearum, the causal fungus of butternut canker disease (BCD), first observed in 1967. Observational evidence in some wild butternut populations indicates that naturalized hybrids of butternut with Japanese walnut (Juglans ailantifolia) may be more tolerant to BCD than pure butternut, but this has not been formally tested in a controlled trial. We aimed to examine potential BCD tolerance within and between pure and hybrid butternut and to determine if there is a difference in canker growth between BCD fungal isolates. Five-year-old pure and hybrid butternut trees were inoculated with two isolates and a blank control. Measurements of both artificially induced and naturally occurring cankers were taken at 8-, 12-, 20-, 24-, and 32-months post-inoculation. Differences in canker presence/absence and size were observed by fungal isolate, which could help explain some of the differences in BCD severity seen between butternut populations. Smaller and fewer cankers and greater genetic gains were seen in hybrid families, demonstrating that hybrids warrant further evaluation as a possible breeding tool for developing BCD-resistant butternut trees.